Порівняня пакетів Blender and Maya - Шеїн, С. О. (ХНУРЕ, 2024)
This work compares two popular platforms for 3D modeling - Blender and Maya. Choose Blender for its free, open source, and active community. Its universality and the possibility of limitation in a number of functions are discussed. Maya's context highlights its status as an industry standard, integration with other Autodesk products, and high-quality tools for precision modeling. The text emphasizes that the choice between them depends on the specific needs and preferences of the user.
Keywords: пакет Blender; пакет Maya